Exploring Verbal Interaction of Non Language Subject Classroom - Ratmanida, Ratmanida; Zainil, Yetty; Ardi, Havid (English Department FBS UNP, 2020)
Given the important role of verbal interaction in teaching and learning process and shaping studentsâ€™ attitude have been the subject of interest of several researchers. The aim of the study was to explore the pattern of verbal Interaction of non language subject at one of the fledgling international standard schools (FISS) in Padang. The site of theÂ study isÂ SMA 1 Padang. Participants of the research were 2 Physics teachers along with their students. Data of this study were drawn from direct classroom observation, and intensive interview; and these data were analyzed quantitatively and qualitatively. The result of study reveals that the highest occurrences of teacher-students interactions patterns are Explanation (E), Asking Question (AQ), and the category of Accept and Used of idea of Pupils (AUIP). Meanwhile, students-teacher interaction consisted of three categories, namely Classical Response (CR), Individual Response (IR), and student initiation (SI). Classical response was found to be the highest occurrence. It indicated that the teacher was still dominated the classroom interaction that needs to be shifted to students-oriented.